Lattices and Lotteries in Apportioning Risk - Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2014)
Although risk aversion has been used in economic models for over 275 years, the past few decades have shown how higher order risk attitudes are also quite important. A behavioral approach to defining such risk attitudes was developed by Eeckhoudt and Schlesinger (2006), based upon simple lottery preference. This article show how the mathematics of lattice theory can be used to model these lottery preferences. In addition to modeling a simple lattice structure, I show how such lattices can be extended in order to develop a better understanding of higher order risk attitudes.
Keywords: D81; 330; risk apportionment; mixed risk aversion; mixed risk loving; lattice theory; submodular function